The Effect Of Regional Allowance And Work Discipline Toward Work Productivity of Employee - Nurtati, Nurtati; Nagara, Patria; Yadewani, Dorris; Dayan, Halimah Putri (ADPEBI International Journal of Business and Social Science, 2023)
This study aims to determine the effect of providing regional allowances and work discipline in increasing employee productivity at the Office of the The Ministry of Financial Management And Regional Income Pariaman City.The data in this study were collected through the distribution of questionnaires, 54 respondents to employees and then the results of the questionnaire data were tested using validity and reliability tests, data analysis techniques using classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing. The results of the t-test research show that (1) the provision of regional allowances has a significant effect on employee work productivity (2) organizational culture has a significant effect on service quality. The results of the f test indicate that the provision of regional allowances and work discipline simultaneously affect the work productivity of employees at The Ministry of Financial Management And Regional Income Pariaman City. It is hoped that government agencies need to increase the provision of regional allowances and improve work discipline so that they continue to work well so that they can increase employee productivity.